Design and Implementation of Display Module for Electronic Navigational Chart Data - GeunHong Park; Daewon Park; Suhyun Park (2014 International Conference on IT Convergence and Security (ICITCS), 2014)
The International Hydrographic Organization (IHO) has presented a new Electronic Navigation Chart(ENC) product specification for S-101, and the paper has covered a study about display module structure. Recently, recognizing the limitations data modeling facility of S-57, IHO developed S-100 as a standard for hydrographic data. Based on S-100 standard, product specifications, including ENC, have been developed. S- 57 based ENC will be replaced by S-101 ENC after S-100 standard has been developed. Display module including S-101 ENC should be replaced, since S-57 based ENC display module have problem expressing S-101 ENC structure. For this transitional period of switching from S-57 standard based toward S-101 standard, we developed a display module that includes S-57 and S-101 standard covering both S-57 ENC data and S-101 ENC data expression.